2000
DOI: 10.1063/1.372700
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and noise characteristics of Co-Cr-Ta films on ultraflat glass substrates for longitudinal recording disks

Abstract: Co–Cr–Ta/Cr bilayered films for longitudinal recording disks were deposited by facing targets sputtering (FTS) on 2.5 in. and ultraflat disk substrates of durable single-crystal silicon at temperature Ts of 100 °C and Ar pressure PAr of 0.2 mTorr. TEM observation of the films revealed ultrafine microstructures, and grain boundaries were unclear. The noise and recording characteristics of those disks were comparable with those of very high-performance disks with Co–Cr–Pt films, with coercivity Hc of 2.4 kOe, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…We consider that the precise tailoring of chemical structures on substrate surfaces is especially important, because it has been demonstrated that functionalized surface often plays a key role in determining the surface morphology [46][47][48][49][50][51][52][53][54], pattern formation [41] and adhesion strength [42][43][44][45] of inorganic coating. Recently, our lab successfully achieved precise tailoring of chemical structures on a polymer surface at molecular level by an extremely simple "confined photocatalytic oxidation" (CPO) reaction [77].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that the precise tailoring of chemical structures on substrate surfaces is especially important, because it has been demonstrated that functionalized surface often plays a key role in determining the surface morphology [46][47][48][49][50][51][52][53][54], pattern formation [41] and adhesion strength [42][43][44][45] of inorganic coating. Recently, our lab successfully achieved precise tailoring of chemical structures on a polymer surface at molecular level by an extremely simple "confined photocatalytic oxidation" (CPO) reaction [77].…”
Section: Introductionmentioning
confidence: 99%
“…The controlled depositions of high quality inorganic oxides on polymeric substrates are often necessary to provide key functions for the devices through themselves, interactions with metals [31] and other oxides [32,33], as well as surface chemical derivations [5,12,13]. For achieving satisfactory applications, such organic/inorganic hybrid materials should possess at least five characters: stable interface adhesion [34][35][36][37], tunable coating thickness [34], the ability of large-area patterning [38,39], low surface roughness [40,41] and high optical transparency [34]. However, polymer surfaces usually have low surface energy and reactivity, irregular molecular orientation and high roughness, and poor thermal and mechanical stabilities, which thus make it difficult to fabricate high quality oxide films upon them [30].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic anisotropy is the foundation to study the appearance of spontaneous magnetization, the mechanism of magnetic reversals and related process. The total anisotropy energy comes from many aspects that closely related to the structure of the materials, such as the shape of the materials, crystalline phase, and elastic strain in material, and so on [12][13][14][15]. Here, a strong PMA is observed only when the t CoFeB is thin because PMA is mainly attributed to interface effects [14].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a model that not only provides insight into magnetron operation but also practical criteria for designing a magnetron is required. Originally, facing targets sputtering (FTS) method was proposed for growing magnetic materials such as Co-Cr, Co-Cr-Ta, and Co-ferrite for perpendicular recording media [6][7][8].…”
Section: Introductionmentioning
confidence: 99%